1993
DOI: 10.3758/bf03211766
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing coefficients of psychophysical power functions

Abstract: Some mathematical properties of coefficients of power functions were analyzed. The size of correlations between intercepts (the logarithm of the coefficient) and exponents depends on the choice of unit of measurement of the physical stimuli. When the mean oflogarithms of a set of responses is uncorre1ated with the exponent, the absolute size of the correlation between the intercept and the exponent increases as the geometric mean of the stimulus measures deviates from one. When the geometric mean is less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…When the exponent decreased, the constant increased.” Indeed, such is the case in the present study (see Table 5), as indicated by the significant negative correlation between both indices, using two different models for line bisection. However, this is neither an anomaly nor a finding – rather a natural consequence of applying the linear model to the data (Glicksohn, 2007; Rule, 1993).…”
Section: Resultsmentioning
confidence: 95%
“…When the exponent decreased, the constant increased.” Indeed, such is the case in the present study (see Table 5), as indicated by the significant negative correlation between both indices, using two different models for line bisection. However, this is neither an anomaly nor a finding – rather a natural consequence of applying the linear model to the data (Glicksohn, 2007; Rule, 1993).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, these linear relationships are virtually identical for perception and memory; the slopes are -0.337 and -0.388 for perception and memory, respectively, adding further force to the view that memory and perception share common properties. However, these analyses of the relationship between the exponent and the multiplicative constant must be viewed cautiously, because Rule (1993) showed that, in the two-parameter power function, the relationship between these two parameters depends on the units used to measure the physical stimuli. Nevertheless, the commonality of the relationship between exponent and multiplicative constant for perception and memory holds independently of Rule's sage theoretical analyses.…”
Section: Multiplicative Constant Additive Constantmentioning
confidence: 99%
“…For example, Equation 6 shows that the proportionality constant α depends on three factors: the reference response (N 0 ) chosen by the participant, the reference sensation chosen by the participant, and the choice of units of measurement for the stimulus (which determines S 0 ). The effect of arbitrary units of measurement was noted by Rule (1993) as a reason why the intercept (i.e., log α) is not simply a subjective unit of measurement. This is clearly shown by Equation 6, in that the proportionality constant is α ϭ N 0 /S 0 β , which shows that α depends on the units of measurement for the physical stimulus (through S 0 ).…”
Section: Magnitude Estimationmentioning
confidence: 99%